How emerging digital technologies affect operations management through co-creation. Empirical evidence from the maritime industry. Issue 16 (10th December 2017) - Agrifoglio, Rocco; Cannavale, Chiara; Laurenza, Elena; Metallo, Concetta
Abstract: Globalization, variation in customer expectations, and the developments connected to Information & Communication Technology are usually considered as the main drivers of changes in Operations Management (OM) strategies by firms in both manufacturing and service industries. Emerging digital technologies, such as Internet of Things or Cloud Computing, represents a novel paradigm that is rapidly affecting on several aspects of everyday-life of private and business users. This paper contributes to extant literature about the relationship between emerging digital technologies and OM, by stressing the value co-creation issue. Specifically, we investigate how emerging digital technologies affect OM through value co-creation in the maritime industry. Our study reports the case of FairWind project, an open technology marine service and graphic user interface enabling sailors to personalize their experience on board through 3rd party boat applications. The case of Fair Wind points out how emerging digital technologies contribute to OM within both organizations and, more in general, maritime industry, as well as the critical role of user's co-creation in defining and managing on-board operations.